Changing roles and statuses of women in Thailand a documentary assessment - Bencha Yoddumnern; Richter, Kerry; Soonthorndhada, Amara; Sethaput, Chanya; Pramualratana, Anthony (IPSR publication, 1992)
Contributed articles.